PENGEMBANGAN KURIKULUM PENDIDIKAN KRISTIANI BAGI ANAK DAN REMAJA GEREJA - Branckly Egbert Picanussa (TANGKOLEH PUTAI, 2018)
Curriculum is one of element of process of Christian Education. There is many arguments of how we develop our curriculum to educate people about Christian faith. Two of the arguments came from D. Campbell Wyckoff and Maria Harris. I hope, this Imaginative Dialogue will help many churches and give informations, especially The Protestant Church of Mollucass, to develop their curriculum to educate people about Christian faith.